The Impact of Entrepreneurial Mindset on Business Growth : A Case Study of Startups in Developing Economies - Rahul Kapoor; Amit Patel; Priya Sharma (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study explores the impact of an entrepreneurial mindset on business growth, with a particular focus on startups in developing economies. Through a case study approach, it examines how entrepreneurial traits such as innovation, risk-taking, and resilience contribute to overcoming challenges unique to these markets, including limited access to resources, unstable regulatory environments, and financial constraints. The research identifies key strategies employed by successful entrepreneurs to drive growth, create competitive advantages, and foster sustainable development. The findings highlight the critical role of entrepreneurial mindset as a catalyst for navigating complexities and achieving scalability in dynamic and resource-constrained environments. This study provides valuable insights for policymakers, educators, and aspiring entrepreneurs aiming to support and enhance the startup ecosystem in developing economies.